The Predisposition, Infection, Response and Organ Dysfunction (PIRO) Scoring System in Predicting Organ Dysfunction and Mortality in Septic Patients - Ahmed Atef; Mohamed Abo Hamela; Mahmoud Khaled; Khaled Hussein (Egyptian Journal of Critical Care Medicine)
Abstract Introduction The predisposition, infection, response, and organ dysfunction (PIRO) staging system was a stratification tool for septic patients. We aimed at assessment of the predictive performance of PIRO score for the development of multiple organ dysfunction, 28-days mortality in sepsis in the intensive care unit (ICU) setting, duration of ICU stay, and ICU readmission within 28 days. Also, to compare PIRO score with the Acute Physiology and Chronic Health Evaluation (APACHE II) and Sequential Organ Failure Assessment (SOFA) scores. Methods Fifty adult patients diagnosed as having systemic sepsis and admitted to ICU were enrolled in the study. PIRO, SOFA, and APACHE II scores were calculated for each patient on the first, second, and third day of admission. Patients were followed up for 28 days. Patients were classified as survivors and non-survivors. Results Twenty-eight patients died, while 22 patients survived till hospital discharge. Three patients readmitted to ICU. The survivors stayed shorter than the non-survivors, (14.9 ±7.5) versus (20.1 ±7.3) days, respectively. In comparison between survivors and non-survivors, APACHE II score was significantly lower in survivors in the second and third days (P=.038 and P=.046, respectively), in survivors PIRO score was significantly lower in second day (P=.039), SOFA score was significantly lower in the first, second, and third days (P value .002, <.002, and <0.003, respectively) and serum lactate was also significantly lower in the first, second, and third days (P value .026, .019, and .030), respectively. Conclusions APACHE II, PIRO, SOFA scores, and serum lactate were valuable tools in predicting 28-day mortality in patients diagnosed as having sepsis.